Whither the Affordable Care Act? - Latham, Stephen R. (The Hastings Center report, 2012)
The U.S. Supreme Court has likely already decided how much, if any, of President Obama's signature Affordable Care Act it is going to strike down as unconstitutional; its holding will be published this summer. No matter what the Court decides, though, it will send state and federal legislators scrambling—either to implement the law or to deal with the consequences of its alteration. There are various decisions the Court might make, but it is still most apt either to leave the ACA standing, or to selectively invalidate some of its mandate-related provisions. In either case, there will be exchanges to design and manage, subsidies to allocate, transparency standards to design and enforce. The Court's decision will thus mark the beginning, not the end, of health reform.